'We're all brave pioneers on this road': a Bourdieusian analysis of field creation for public health adaptation to climate change in Ontario, Canada. Issue 1 (1st January 2021) - Buse, Chris G; Poland, Blake; Wong, Josephine; Haluza-Delay, Randolph
ABSTRACT: Despite significant engagement with new and emerging issues in public health practice, the public health literature has few theoretical explanations for how new practices emerge, take root, and become institutionalized. In this contribution, we utilize Pierre Bourdieu's sociological concepts of field, habitus and capital, and in-depth interviews with public health practitioners to document and describe the emerging field of public health adaptation to climate change Ontario, Canada. In doing so, we identify and explain three types of climate change action and associated practices – 'wait and see', repackaging existing actions and championing new actions – that practitioners relate to climate change adaptation in Ontario (i.e. business as usual, repackaging existing actions and championing climate new actions). We discuss the typology in relation to the dominant and emerging logics that practitioners ascribe to promoting practical action on this sub-field of environmental health practice to promote a discussion of how social change occurs within a well-established field of professional practice. Findings suggest, that change and innovation can result from exogenous shocks that force practitioners to adopt new practices (e.g. the increasing frequency and intensity of climate-related impacts on health), how the 'rules' of a given field are interpreted by practitioners and made actionable, and through the negotiation of new rules by practitioners with a 'radical habitus' who champion particular issues, albeit resulting in significant professional risk. We discuss these findings in relation to Bourdieu's theory, concluding there is significant room for practitioner agency to cultivate normative dispositions and influence the adoption of policy and practice-change.